2021
DOI: 10.1038/s41417-020-00288-z
|View full text |Cite
|
Sign up to set email alerts
|

CHD1 loss negatively influences metastasis-free survival in R0-resected prostate cancer patients and promotes spontaneous metastasis in vivo

Abstract: The outcome of prostate cancer (PCa) patients is highly variable and depends on whether or not distant metastases occur. Multiple chromosomal deletions have been linked to early tumor marker PSA recurrence (biochemical relapse, BCR) after radical prostatectomy (RP), but their potential role for distant metastasis formation is largely unknown. Here, we specifically analyzed whether deletion of the tumor suppressor CHD1 (5q21) influences the post-surgical risk of distant metastasis and whether CHD1 loss directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Of note, early states of each subtype had similar favorable prognosis, while both late states showed similar unfavorable prognosis (Supplemental Figure 16). Endpoints of biochemical recurrence-free survival and PCa-specific mortality-free survival rates followed similar patterns (Supplemental Figure 17), consistent with previous findings (7,43). These results show that genomic alterations defined as late progression events at the molecular level also show clear evidence of more aggressive disease, consistent with clinical progression.…”
Section: Introductionsupporting
confidence: 89%
“…Of note, early states of each subtype had similar favorable prognosis, while both late states showed similar unfavorable prognosis (Supplemental Figure 16). Endpoints of biochemical recurrence-free survival and PCa-specific mortality-free survival rates followed similar patterns (Supplemental Figure 17), consistent with previous findings (7,43). These results show that genomic alterations defined as late progression events at the molecular level also show clear evidence of more aggressive disease, consistent with clinical progression.…”
Section: Introductionsupporting
confidence: 89%
“…Among the chromatin regulators/transcription factors, BACH1, CTBP2, HDAC2, KDM4A, MYC, RAD21, and SUZ12 have been known to play roles in cancer proliferation, whereas CHD1, CHD2, and ZBTB7A have been reported as tumor suppressors exemplified in Ref. 27 , 28 , 29 , 30 , 31 , 32 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the deletion of CHD1 has been associated with cancer and postoperative biochemical relapse (BCR) in a cohort of prostate cancer (PCa) patients, suggesting it is a poor prognosis marker [36]. Recent research by Oh-Hohenhorst et al revealed that CHD1 loss increases the risk of postoperative metastasis in R0-resected PCa patients and promotes spontaneous metastasis formation in vivo [37]. In a study investigating CHD1's potential roles in breast cancer, researchers introduced shRNA-mediated depletion of CHD1 into both PTEN-deficient and PTEN-intact breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%